Influence of the Percentage of TiO2 Doped into SiO2 Matrix on Photocatalysis. (25th September 2012) - da Silva, L. M. L.; Silva, F. da C.; de Carvalho, A. L.; Marçal, L.; Saltarelli, M.; De Faria, E. H.; Rocha, L. A.; Calefi, P. S.; Ciuffi, K. J.; Nassar, E. J.
Abstract : The sol-gel process was employed in the preparation of titania-doped spherical nanosilica for application in photocatalysis. To this end, the silica matrix was doped with 1 and 10% titania, and the catalytic activity of the resulting solids in the degradation of rhodamine was tested. The synthesized materials were thermally treated at 120, 400, and 800°C. Differential thermal analysis did not evidence the titania-phase transition from anatase to rutile. Scanning electron microscopy revealed the formation of monodisperse spherical nanoparticles with sizes varying between 400 and 500 nm. The UV-Vis absorption spectra showed that the silica doped with 10% titania promoted 86% rhodamine degradation within 90 minutes, as compared to 40% in the case of the silica containing 1% titania. The silica matrix was demonstrated to affect the titania-phase transformation.